Neurological manifestations of SARS-CoV-2 with special focus on anosmia - Starker, Simon (Jihočeská univerzita, 2021)
The overall aim of the thesis is to explore and categorize currently known neurological symptoms associated with SARS-CoV-2 infection. It should be delved in more detail in SARS-CoV-2-associated loss off smell that has been reported, which is in some countries used as a marker for COVID-19. In particular, the existing evidence should be weighed for neuronal and non-neuronal origin of anosmia, and it should be hinted on the possible mechanism underlying this olfactory perturbation.
Neurological manifestations of SARS-CoV-2 with special focus on anosmia
Keywords: 'COVID-19'; 'SARS-CoV-2'; 'SARS'; 'neurological symptoms'; 'anosmia'; 'loss of smell'; 'CNS'; 'PNS'; 'ACE2'; 'Olfactory dysfunction'; etc